Biochemical and functional characterization of glycosaminoglycans released from degranulating rat peritoneal mast cells: Insights into the physiological role of endogenous heparin. (December 2016) - Lever, Rebecca; Smailbegovic, Amir; Riffo-Vasquez, Yanira; Gray, Elaine; Hogwood, John; Francis, Stephen M.; Richardson, Neville V.; Page, Clive P.; Mulloy, Barbara
Abstract: The properties of commercially prepared heparin as an anticoagulant and antithrombotic agent in medicine are better understood than is the physiological role of heparin in its native form, where it is uniquely found in the secretory granules of mast cells. In the present study we have isolated and characterised the glycosaminoglycans (GAGs) released from degranulating rat peritoneal mast cells. Analysis of the GAGs by NMR spectroscopy showed the presence of both heparin and the galactosaminoglycan dermatan sulphate; heparinase digestion profiles and measurements of anticoagulant activity were consistent with this finding. The rat peritoneal mast cell GAGs significantly inhibited accumulation of leukocytes in the rat peritoneal cavity in response to IL-1β (p < 0.05, n = 6/group), and inhibited adhesion and diapedesis of leukocytes in the inflamed rat cremasteric microcirculation in response to LPS (p < 0.001, n = 4/group). FTIR spectra of human umbilical vein endothelial cells (HUVECs) were altered by treatment of the cells with heparin degrading enzymes, and restored by the addition of exogenous heparin. In conclusion, we have shown that rat peritoneal mast cells contain a mixture of GAGs that possess anticoagulant and anti-inflammatory properties.